Preparation of Zinc Oxide/Graphite Composite Using Solid-State Method as an Anode Material for Lithium-Ion Battery - Hanaiyah Parasdila; Anisa Surya Wijareni; Hendri Widiyandari (Jurnal Kimia Sains dan Aplikasi, 2022)
Lithium-ion batteries using zinc oxide (ZnO) as anode material had a high theoretical capacity of about 987 mAh/g. Unfortunately, ZnO capacity can drop below 200 mAh/g after only a few cycles. For that reason, graphite was added in this study due to its stable theoretical capacity of around 348-374 mAh/g to maintain the stability of lithium-ion battery capacity. Zinc oxide/graphite (ZnO/Graphite) was prepared using a solid-state method, in which ZnO and graphite were mortared until homogeneous with the mass ratio of (2:1), (1:1), and (1:2). The SEM images of all samples showed the agglomerate morphology between ZnO and graphite which affect the results of the battery performance test. The final result of the ZnO/Graphite anode can be considered a continuous anode material due to the stable cycle performance obtained in the range of 219.72–371.27 mAh/g with a decreased value of 40% after 55 cycles.